1998
DOI: 10.1046/j.1365-2567.1998.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk between Vβ8+ and γδ+ T lymphocytes in contact sensitivity

Abstract: We have previously reported that T lymphocytes proliferating in vitro to the hapten trinitrochlorobenzene (TNCB) exhibit a very restricted V beta gene usage and response to TNCB is limited to T-cell receptors (TCR) composed of V beta 8.2 in combination with V alpha 3.2, V alpha 8 and V alpha 10. This paper investigates the role played by T lymphocytes expressing the V beta 8.2 gene segment in the contact sensitivity (CS) reaction to TNCB in the intact mouse and in its passive transfer into naive recipient mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
6
35
0
Order By: Relevance
“…5]for a recent review]. Cross-talk between γδ T cells and other cells of the immune system has been shown to modulate humoral [64, 65]and cellular immune responses [66, 67, 68, 69]. Our own in vitro experiments indicate a bidirectional interaction between phosphoantigen-reactive Vγ9/Vδ2 γδ T cells and CD4+ αβ T cells.…”
Section: Possible Functions Of γδ T Cellsmentioning
confidence: 85%
“…5]for a recent review]. Cross-talk between γδ T cells and other cells of the immune system has been shown to modulate humoral [64, 65]and cellular immune responses [66, 67, 68, 69]. Our own in vitro experiments indicate a bidirectional interaction between phosphoantigen-reactive Vγ9/Vδ2 γδ T cells and CD4+ αβ T cells.…”
Section: Possible Functions Of γδ T Cellsmentioning
confidence: 85%
“…In keeping with this cytotoxicity was the observation that animals receiving nondepleted LNC had higher clinical scores and more prominent lesion activity, the milder scores being associated with less destructive inflammatory lesions in which primary demyelination was the major feature, and the most severe of which were accompanied by widespread CNS lesions that were highly destructive, leading to total loss of nerve fibers. In addition to a proposed effector function, ␥␦ T cells have also been shown to possess important immunoregulatory activities (25)(26)(27)(28)(29)(30)(31)(32). For example, in contact hypersensitivity, the presence of ␥␦ T cells was responsible for transfer of hypersensitivity to naive animals (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, aside from this effector function, ␥␦ T cells seem to be important regulatory elements of the immune system (25). It has been shown that ␥␦ T lymphocytes are capable of enhancing inflammatory responses in autoimmune diseases, e.g., systemic lupus erythematosus, rheumatoid arthritis (25,26), graft-vs-host disease (27), and delayed-type hypersensitivity (28,29). In addition, ␥␦ T cells are involved in the mechanism of immune tolerance induced by oral (30) or high-dose i.v.…”
mentioning
confidence: 99%
“…51,52 Experimental evidence supports the concept of cooperation, or`cross talk' between ab and gd T cells. 53 It follows from these observations that the simultaneous analysis of CDR3 expression in these T cell subsets may improve our knowledge of how these mechanisms contribute to autoimmunity.…”
Section: Discussionmentioning
confidence: 99%